The adaptive benefits of agricultural water markets in California. (25th March 2021) - Arellano-Gonzalez, Jesus; AghaKouchak, Amir; Levy, Morgan C; Qin, Yue; Burney, Jennifer; Davis, Steven J; Moore, Frances C
Abstract: Climate change is expected to increase the scarcity and variability of fresh water supplies in some regions with important implications for irrigated agriculture. By allowing for increased flexibility in response to scarcity and by incentivizing the allocation of water to higher value use, markets can play an important role in limiting the economic losses associated with droughts. Using data on water demand, the seniority of water rights, county agricultural reports, high-resolution data on cropping patterns, and agronomic estimates of crop water requirements, we estimate the benefits of market-based allocations of surface water for California's Central Valley. Specifically, we estimate the value of irrigation water and compare the agricultural costs of water shortages under the existing legal framework and under an alternate system that allows for trading of water. We find that a more efficient allocation of curtailments could reduce the costs of water shortages by as much as 362 million dollars per year or 4.4% of the net agricultural revenue in California in expectation, implying that institutional and market reform may offer important opportunities for adaptation.